Edward Bernard’s Chinese map - Poole, W (Taylor and Francis, 2019)
This article assembles scattered pieces of evidence to demonstrate that the famous Chinese “Selden map”, acquired by the Bodleian Library in 1659, was duplicated in the later seventeenth century by the Oxford mathematician and orientalist Edward Bernard (1673–91), as part of his abortive attempt to edit a definitive corpus of classical and post-classical mathematical texts. It was Bernard’s copy, and not the original Selden map, that was publicly exhibited in Oxford in the eighteenth century. Some discussion is also furnished of other Chinese maps received in contemporary Oxford comparable to the Selden map, notably what I name the “Brown/Styleman” map, presented to the Bodleian Library in 1698. These discussions will help us to rethink how contemporary European scholars might have approached oriental maps.